Sclerosing adenosis and radial scar of breast : Imaging findings and breast cancer association - Sakolnurak, Mutita; Boonjunwetwat, Darunee (Chulalongkorn Medical Journal, 2023)
Background : Sclerosing adenosis and radial scar of the breast are benign conditions that may be mistaken for carcinoma on imaging and they are also considered independent risk for breast cancer. Objective : To demonstrate mammographic and ultrasonographic patterns of sclerosing adenosis and radial scar and to determinate the coexisting of both diseases to synchronous breast cancer. Material and Methods : Retrospective analysis of the pathology confirmed 80 sclerosing adenosis foci and 23 radial scar foci was performed. The mammographic and ultrasound features of each focus were analyzed. Coexisting of breast malignancy is also recorded. The result was reported descriptively. Results : - Mammographic findings of sclerosing adenosis are 34 foci (47.22%) of mass, 35 foci (48.61%) of abnormal calcifications, 8 foci (11.11%) of focal distortion, 8 foci (11.11%) of focal asymmetry and no mammographic abnormality in 12 foci (16.67%). Ultrasonographic findings of sclerosing adenosis are 68 foci (86.07%) of mass, 7 foci (8.66%) of calcifications, 7 foci (8.86%) of focal thick duct and no sonographic abnormality in 8 foci (10.13%). - Mammographic findings of radial scar are 7 foci (30.43%) of mass, 9 foci (39.13%) of abnormal calcifications, 6 foci (26.09%) of focal distortion, 6 foci (26.09%) of focal asymmetry and no mammographic abnormality in 2 foci (8.70%). Ultrasonographic findings of radial scar are 15 foci (68.18%) of mass, 2 foci (9.09%) of calcifications, 1 focus (4.34%) of focal shadowing and 6 foci (27.27%) without sonographic abnormality. Neither mammographic nor sonographic abnormality is seen in one radial scar. Most lesions in our study are categorized as BI-RADS 4 and 5. Coexisting breast cancer with sclerosing adenosis and radial scar are 17.5% and 8.69%, respectively. Conclusion : There are varying appearances of sclerosing adenosis and radial scar on mammographic and ultrasound. Both sclerosing adenosis and radial scar are usually categorized as BI-RADS 4 and 5. There is no definite imaging characteristics of which can distinguish them from malignant lesion. Coexisting of breast cancer in these patients is higher than usual screening mammogram.